LOS BIOHERMAS OSTREROS DE LA FORMACION ROCA (PALEOCENO) EN EL SUDOESTE DE LA PROVINCIA DE LA PAMPA, ARGENTINA (Ameghiniana, 2014)
The presence of numerous bodies placed in sediments of the Roca Formation -in the Cerros Bayos area, Puelen Departament, La Pampa province, Argentine Republic, are reported in this paper for the first time. The cited bodies are classified as mixed skeletal oyster bioherms and are the result of calcium carbonate deposition via oysters and other invertebrates debris within sediments of different nature. Paleoecological and paleoenvironmetal conclusions regarding water temperature, circulation, salinity and depth, as well as topography of the sea botton are given. On the basis of ·microfossil content, it is pointed out that the age of the Roca Formation in Cerros Bayos is regarded as Early Tertiary (Danian)